Enantioselective Synthesis of α-Chiral Amides by Catalytic Hydrogenation with Iridium N,P-Complexes - Peters, Bram B. C.; Birke, Norman; Massaro, Luca; Andersson, Pher G. (Synlett, 2022)
The catalytic asymmetric hydrogenation of olefins constitutes a powerful method for the preparation of chiral compounds. A series of prochiral unsaturated amides were efficiently reduced with high enantioselectivities by means of an iridium N,P-complex-catalyzed hydrogenation. Its application in the synthesis of fenpropidin and the possibility of using isomeric mixtures of starting materials are attractive features of the method.
Keywords: amides; enantioselectivity; iridium catalysis; asymmetric catalysis; hydrogenation